2019
DOI: 10.1021/acsenergylett.9b00430
|View full text |Cite
|
Sign up to set email alerts
|

Cathode-Supported All-Solid-State Lithium–Sulfur Batteries with High Cell-Level Energy Density

Abstract: Bulk-type all-solid-state lithium batteries (ASSLBs) are being considered as a promising technology to improve the safety and energy density of today's batteries. However, current bulk-type ASSLBs suffer from low cell-level energy density due to the challenges in reducing the electrolyte thickness. In this work, we report cathode-supported ASSLBs with a thin solid electrolyte layer. Starting from a stainless steel mesh-supported Li 2 S cathode, we are able to build an ASSLB with a ∼100 μm thick Li 3 PS 4 elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
133
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(150 citation statements)
references
References 36 publications
4
133
0
1
Order By: Relevance
“…Furthermore, when considering the cell‐level energy density of the S/PAN|LCE|Li in this work, the specific gravimetric energy density ( E g ) and the volumetric energy density ( E v ) were calculated according to Equations (S1) and (S2) in the Supporting Information. The calculated E g and E v of the S/PAN|LCE|Li cell amount to 116 Wh kg −1 and 660 Wh L −1 , respectively, which is higher than the most reported solid‐state cells in the literature 50…”
Section: Resultsmentioning
confidence: 60%
“…Furthermore, when considering the cell‐level energy density of the S/PAN|LCE|Li in this work, the specific gravimetric energy density ( E g ) and the volumetric energy density ( E v ) were calculated according to Equations (S1) and (S2) in the Supporting Information. The calculated E g and E v of the S/PAN|LCE|Li cell amount to 116 Wh kg −1 and 660 Wh L −1 , respectively, which is higher than the most reported solid‐state cells in the literature 50…”
Section: Resultsmentioning
confidence: 60%
“…The mass ratio of SSEs to cathode sulfur is 2 so that the thicknesses of cathode plate and solid‐state electrolyte layer are roughly equal. [ 167a ] The mole ratio of Li metal anode to sulfur in the cathode is 3, meaning that there is 50% lithium excess to ensure the effective utilization of sulfur. An over‐average specific capacity of 1200 mAh g −1 , about three‐quarters of the theoretical level, is appropriate for evaluating practical pouch cell performance.…”
Section: Cathode Preparationmentioning
confidence: 99%
“…26 Bulk Kevlar fiber is not suitable for film processing because it tends to aggregate, which would result in SSE films with undesirable heterogeneities. Several teams have proposed using a non-woven (NW) paper made from aramid fibers as reinforcement for cold pressed SSEs in allsolid-state batteries 27,28 and a similar approach is taken here by replacing bulk Kevlar fiber with an inexpensive NW fiberglass paper. Herein, it is shown that reinforced (Li 2 S) 60 (SiS 2 ) 28 (P 2 S 5 ) 12 glass separators can be fabricated by hot pressing at 330°C and 12 MPa.…”
mentioning
confidence: 99%